Analisa Keanekaragaman dan Karakteristik Morfologi Famili Cyperaceae di Kawasan Perumahan Rajasanagara, Cibiru, Bandung - Fahra Annisa Putri; Falak Agung Nugraha; Ateng Supriatna (Universitas Katolik Widya Karya Malang, 2023)
Cyperaceae is a family of liliopsida plants. Plants belonging to the cyperaaceae are a puzzle. This study aims to determine the diversity and morphological characteristics of the Cyperaceae family in the Rajasanagara Cibiru Residential Area, Bandung. The research was carried out by direct observation, then the results of these observations were described. Cyperus species were found with the species cyperus alternifolius and cyperus kyllingia. The two species have similarities and differences respectively.